Characteristics of Neonatal Intracranial Hemorrhage at RSUP Haji Adam Malik during the Year 2022-April 2025 - Caroline Alma Cahyadi; Abdurrahman Mousa; Deske Muhadi Rangkuti; Rina Yunita (Talenta Universitas Sumatera Utara, 2025)
The neonatal state is a vulnerable period where rapid physiological transitions happen. In Indonesia, in the year 2020, the Infant Mortality Rate was 19.83 per 1,000 live births, including a Neonatal Mortality Rate of 9.30. This state is also a part of the critical period of a postnatal brain development. Disruption to the brain during this time window can cause problems in the neurodevelopmental process. One of the examples being intracranial hemorrhage in neonates, which the true prevalence and incidence rates of are unclear, but which have high mortality and morbidity rates. The objective this study is to determine the characteristics of neonatal intracranial hemorrhage at Haji Adam Malik General Hospital in 2022-April 2025. This study used a descriptive design through a retrospective cross-sectional study and a sample of neonates with intracranial hemorrhage at Haji Adam Malik General Hospital through saturated sampling. It was found that incidence rate was 6.24 per 100, with the most common bleeding location being intraventricular 25 (89.3%), the majority of neonates were premature, namely 19 (67.9%), low birth weight 19 (67.9%), the most common symptoms were seizures and respiratory distress 15 (53.6%), and 11 (39.3%) neonates made a good recovery.